600MPa strength grade high strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material and preparation method
By adopting specific component design and preparation processes in aluminum-based composite materials, the shortcomings of high-strength aluminum-based composite materials in resisting intergranular corrosion are solved, and high-strength and low intergranular corrosion depths of 600MPa strength level are achieved, meeting the needs of high-performance materials in the fields of aerospace and other fields.
Patent Information
- Application Number
- CN202210438213.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-04-25
AI Technical Summary
The existing high-strength aluminum-based composite materials have poor performance in resisting intergranular corrosion, resulting in limited service life and safety. The composition design and preparation method of 600MPa strength grade high-strength high-strength high-corrosion corrosion-resistant B4Cp-reinforced aluminum-based composite materials with no independent intellectual property rights.
Through component design and preparation and processing technology, 600MPa strength grade high strength and high resistance to intergranular corrosion B4Cp reinforced aluminum composite material was prepared by using 7.5vol.% boron carbide particles (B4Cp), 52.5vol.% homemade Ti alloy 7000 series aluminum alloy and 40vol.% homemade Ti alloy 7000 series aluminum alloy. Combined with composite material powder preparation, ingot preparation, plastic deformation processing and toughening heat treatment technology, a 600MPa strength grade high strength and high resistance to intergranular corrosion B4Cp reinforced aluminum composite material was prepared.
It has achieved a 610.98MPa tensile strength of aluminum-based composite materials and a low intergranular corrosion depth of 84.1μm, meeting the needs of high-performance materials in the fields of aerospace and weapons and equipment, and breaking foreign technology blockade.
Smart Images

Figure CN116144992B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum-based composite material, in particular to a novel aluminum-based composite material and a preparation method thereof, specifically to a 600MPa strength-grade high-strength and high-intergranular corrosion-resistant B4Cp reinforced aluminum-based composite material and a preparation method thereof. Background Art
[0002] The aerospace and military industries have an eternal demand for lightweight, high-rigidity, and high-strength materials. The development of lightweight, high-rigidity, and high-strength materials with higher performance has always been a high-tech field that countries around the world have prioritized.
[0003] B4Cp reinforced aluminum-based composite materials are the most typical lightweight, high-rigidity and high-strength materials. They have a series of characteristics such as low specific gravity, high specific elastic modulus, high specific strength, heat resistance and fatigue resistance. They play an irreplaceable role in aerospace, military industry and other fields.
[0004] As we all know, there is usually an inverse relationship between the strength, plasticity and corrosion resistance of aluminum-based composite materials. Intergranular corrosion is a common corrosion form of high-strength aluminum-based composite materials, and it is also a basic corrosion form, which greatly damages the service life and safety of high-strength aluminum-based composite materials. Generally speaking, the higher the strength of high-strength aluminum-based composite materials, the lower the intergranular corrosion performance. The intergranular corrosion depth of existing high-strength aluminum-based composite materials is generally much higher than 200μm.
[0005] So far, there is no composition design and preparation method of 600MPa strength-grade high-strength and high-intergranular corrosion-resistant B4Cp reinforced aluminum-based composite materials with independent intellectual property rights available, which to a certain extent restricts the development of my country's aerospace, weapon equipment and other industries. Summary of the invention
[0006] The purpose of the present invention is to invent a 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material and a preparation method thereof through component design and preparation and processing technology design.
[0007] One of the technical solutions of the present invention is:
[0008] A 600MPa strength grade, high-strength, high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material, characterized in that it is mainly composed of boron carbide particles (B4Cp) as reinforcement, a homemade Ti-free alloyed 7000 series aluminum alloy and a homemade Ti-alloyed 7000 series aluminum alloy, wherein the volume percentage of the boron carbide particles (B4Cp) is 7.5vol.%, the volume percentage of the homemade Ti-free alloyed 7000 series aluminum alloy is 52.5vol.%, and the volume percentage of the homemade Ti-alloyed 7000 series aluminum alloy is 40vol.%.
[0009] The self-made Ti-free alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), and copper (Cu), wherein the mass percentage of zinc (Zn) is 8.85%, the mass percentage of magnesium (Mg) is 2.05%, the mass percentage of copper (Cu) is 0.439%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%.
[0010] The self-made Ti alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), copper (Cu), strontium (Sr), zirconium (Zr), and titanium (Ti), wherein the mass percentage of zinc (Zn) is 11.94%, the mass percentage of magnesium (Mg) is 3.1%, the mass percentage of copper (Cu) is 1.25%, the mass percentage of strontium (Sr) is 0.0267%, the mass percentage of zirconium (Zr) is 0.249%, the mass percentage of titanium (Ti) is 1.605%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%.
[0011] The second technical solution of the present invention is:
[0012] A method for preparing a 600MPa strength grade high-strength and high intergranular corrosion resistant B4Cp reinforced aluminum-based composite material, characterized in that it comprises the following steps in sequence: (1) preparing composite material powder; (2) preparing composite material ingot; (3) plastic deformation processing; and (4) strengthening and toughening heat treatment.
[0013] The preparation process of the composite material powder is as follows: stirring the reinforcement in ethanol, ultrasonically dispersing the reinforcement, wet grinding the reinforcement, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; the composite material powder is obtained;
[0014] The composite material ingot preparation is characterized by: the composite material ingot is prepared by the method of "cold isostatic pressing (CIP) - vacuuming the jacket - hot isostatic pressing (HIP)"; the final temperature of vacuuming the jacket is 550°C, the temperature of HIP is 525°C, the time is 4h, and the pressure is 140MPa;
[0015] The plastic deformation processing is characterized by: secondary extrusion, the first extrusion is a jacket hot extrusion, the extrusion ratio is 10:1, the extrusion temperature is 480°C, and the jacket material is 6061Al; the second extrusion is a jacket-free extrusion, the extrusion ratio is 10:1, and the extrusion temperature is 440°C;
[0016] The toughening heat treatment is characterized by: annealing treatment + solution treatment + aging treatment; the annealing process is 250℃×6h+350℃×6h+450℃×12h insulation and then furnace cooling, the solution treatment process is
[0017] 460℃×2h+470℃×2h+480℃×2h+490℃×2h or
[0018] 460℃×2h+470℃×2h+480℃×2h+490℃×2h+500℃×2h+510℃×2h or
[0019] After keeping at 460℃×2h+470℃×2h+480℃×2h, the material is water quenched at room temperature, and the aging process is natural aging or artificial aging at 150℃. A 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material can be obtained.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention obtains a composition of a 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material and a preparation method thereof.
[0022] (2) The aluminum-based composite material of the present invention has a tensile strength of up to 610.98 MPa, and a post-fracture elongation of 3.4%. According to the national standard GB / T 7998-2005 (aluminum alloy intergranular corrosion determination method), the intergranular corrosion depth is 84.1 μm.
[0023] (3) The present invention discloses the composition and preparation method of a 600MPa strength grade high-strength and high intergranular corrosion resistant B4Cp reinforced aluminum-based composite material, which to a certain extent breaks the foreign technical blockade of high-performance aluminum-based composite materials and can meet the needs of my country's aerospace, weapon equipment and other fields.
[0024] (4) The present invention has obtained an ideal preparation method through a large number of experiments, especially by controlling the content of each component by adding each intermediate alloy and pure metal in sequence. According to the process of the present invention, an aluminum-based composite material that meets the requirements can be easily obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cross-sectional metallographic image of Example 1 of the present invention after the T4 (natural aging) intergranular corrosion test.
[0026] Figure 2 This is a cross-sectional metallographic image of comparative example 1 of the present invention after the annealed intergranular corrosion test.
[0027] Figure 3 This is a cross-sectional metallographic image of comparative example 2 of the present invention after the annealing intergranular corrosion test.
[0028] Figure 4 It is a cross-sectional metallographic image of comparative example 3 of the present invention after the T4 (natural aging) intergranular corrosion test. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0030] Embodiment 1.
[0031] A 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material is prepared by the following method:
[0032] First, composite material powder is prepared, and the process is as follows: stirring B4Cp reinforcement, ultrasonic dispersion reinforcement, wet grinding reinforcement in ethanol, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; that is, composite material powder is obtained; wet grinding, drying, dry grinding, sieving powder and other processes are the same as the existing technology, and wet grinding parameters, drying temperature, dry grinding parameters, sieving powder mesh aperture and the like are all conventional process parameters; the self-made Ti-free alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), and copper (Cu), wherein the mass percentage of zinc (Zn) is 8.85%, the mass percentage of magnesium (Mg) is 2.05%, the mass percentage of copper (Cu) is 0.439%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%. The self-made Ti alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), copper (Cu), strontium (Sr), zirconium (Zr), and titanium (Ti), wherein the mass percentage of zinc (Zn) is 11.94%, the mass percentage of magnesium (Mg) is 3.1%, the mass percentage of copper (Cu) is 1.25%, the mass percentage of strontium (Sr) is 0.0267%, the mass percentage of zirconium (Zr) is 0.249%, the mass percentage of titanium (Ti) is 1.605%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%.
[0033] Secondly, the composite ingot is prepared by adopting the method of "cold isostatic pressing (CIP) - vacuuming the jacket - hot isostatic pressing (HIP)" to prepare the composite ingot; the final temperature of vacuuming the jacket is 550°C, the temperature of HIP is 525°C, the time is 4h, and the pressure is 140MPa;
[0034] Third, plastic deformation processing is performed using secondary extrusion. The first extrusion is hot extrusion with a sheath, an extrusion ratio of 10:1, an extrusion temperature of 480°C, and the sheath material is 6061Al; the second extrusion is hot extrusion without a sheath, an extrusion ratio of 10:1, and an extrusion temperature of 440°C;
[0035] Fourth, strengthening and toughening heat treatment, using annealing treatment + solution treatment + aging treatment; the annealing treatment process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace, the solution treatment process is 460℃×2h+470℃×2h+480℃×2h+490℃×2h insulation and then room temperature water quenching, the aging treatment process is natural aging (T4).
[0036] The 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material can be obtained.
[0037] The aluminum-based composite material of this embodiment has the following components: 7.5 vol.% B4Cp, 52.5 vol.% 7055Al, and 40 vol.% self-made Ti-alloyed 7000 series aluminum alloy.
[0038] The aluminum-based composite material of this embodiment has a tensile strength of 610.98 MPa in the T4 (natural aging) state and an elongation of 3.4%. According to the national standard GB / T 7998-2005 (determination method for intergranular corrosion of aluminum alloys), the intergranular corrosion depth is 84.1 μm ( Figure 1 ).
[0039] Embodiment 2.
[0040] A 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material is prepared by the following method:
[0041] First, composite material powder is prepared, and the process is as follows: stirring reinforcement in ethanol, ultrasonically dispersing B4Cp reinforcement, wet grinding reinforcement, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; that is, composite material powder is obtained; similarly, the wet grinding, drying, dry grinding, sieving powder and other processes are the same as the existing technology, and the wet grinding parameters, drying temperature, dry grinding parameters, sieving powder mesh aperture and the like are all conventional process parameters; the self-made Ti-free alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), and copper (Cu), wherein the mass percentage of zinc (Zn) is 8.85%, the mass percentage of magnesium (Mg) is 2.05%, the mass percentage of copper (Cu) is 0.439%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%. The self-made Ti alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), copper (Cu), strontium (Sr), zirconium (Zr), and titanium (Ti), wherein the mass percentage of zinc (Zn) is 11.94%, the mass percentage of magnesium (Mg) is 3.1%, the mass percentage of copper (Cu) is 1.25%, the mass percentage of strontium (Sr) is 0.0267%, the mass percentage of zirconium (Zr) is 0.249%, the mass percentage of titanium (Ti) is 1.605%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%.
[0042] Secondly, composite ingots were prepared by the method of "cold isostatic pressing (CIP) - vacuum packing - hot isostatic pressing (HIP)"; the final temperature of vacuum packing was 550°C, the temperature of HIP was 525°C, the time was 4h, and the pressure was 140MPa;
[0043] Third, plastic deformation processing is performed using secondary extrusion. The first extrusion is hot extrusion with a sheath, an extrusion ratio of 10:1, an extrusion temperature of 480°C, and the sheath material is 6061Al; the second extrusion is hot extrusion without a sheath, an extrusion ratio of 10:1, and an extrusion temperature of 440°C;
[0044] Fourth, strengthening and toughening heat treatment, using annealing treatment + solution treatment + aging treatment; the annealing treatment process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace, the solution treatment process is 460℃×2h+470℃×2h+480℃×2h+490℃×2h+500℃×2h+510℃×2h insulation and then room temperature water quenching, the aging treatment process is natural aging (T4).
[0045] The 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material can be obtained.
[0046] The aluminum-based composite material of this embodiment has the following components: 7.5 vol.% B4Cp, 52.5 vol.% 7055Al, and 40 vol.% self-made Ti-alloyed 7000 series aluminum alloy.
[0047] The aluminum-based composite material of this embodiment has a tensile strength of 597.45 MPa in the T4 (natural aging) state and an elongation after fracture of 2.8%.
[0048] Embodiment three.
[0049] A 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material is prepared by the following method:
[0050] First, composite material powder is prepared, and the process is as follows: stirring B4Cp reinforcement, ultrasonic dispersion reinforcement, wet grinding reinforcement in ethanol, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, powder screening, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, powder screening again, and vacuum drying; that is, composite material powder is obtained; the wet grinding, drying, dry grinding, powder screening and other processes are the same as the existing technology, and the wet grinding parameters, drying temperature, dry grinding parameters, powder screening mesh aperture and the like are all conventional process parameters; the self-made Ti-free alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), and copper (Cu), wherein the mass percentage of zinc (Zn) is 8.85%, the mass percentage of magnesium (Mg) is 2.05%, the mass percentage of copper (Cu) is 0.439%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%. The self-made Ti alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), copper (Cu), strontium (Sr), zirconium (Zr), and titanium (Ti), wherein the mass percentage of zinc (Zn) is 11.94%, the mass percentage of magnesium (Mg) is 3.1%, the mass percentage of copper (Cu) is 1.25%, the mass percentage of strontium (Sr) is 0.0267%, the mass percentage of zirconium (Zr) is 0.249%, the mass percentage of titanium (Ti) is 1.605%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%.
[0051] Secondly, composite ingots were prepared by the method of "cold isostatic pressing (CIP) - vacuum packing - hot isostatic pressing (HIP)"; the final temperature of vacuum packing was 550°C, the temperature of HIP was 525°C, the time was 4h, and the pressure was 140MPa;
[0052] Third, plastic deformation processing is performed using secondary extrusion. The first extrusion is hot extrusion with a sheath, an extrusion ratio of 10:1, an extrusion temperature of 480°C, and the sheath material is 6061Al; the second extrusion is hot extrusion without a sheath, an extrusion ratio of 10:1, and an extrusion temperature of 440°C;
[0053] Fourth, strengthening and toughening heat treatment, annealing treatment + solution treatment + aging treatment; the annealing treatment process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace, the solution treatment process is 460℃×2h+470℃×2h+480℃×2h insulation and then room temperature water quenching, and the aging treatment process is natural aging (T4).
[0054] The 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material can be obtained.
[0055] The aluminum-based composite material of this embodiment has the following components: 7.5 vol.% B4Cp, 52.5 vol.% self-made Ti-free 7000 series aluminum alloy, and 40 vol.% self-made Ti-alloyed 7000 series aluminum alloy.
[0056] The aluminum-based composite material of this embodiment has a tensile strength of 581.54 MPa in the T4 (natural aging) state and an elongation after fracture of 2.7%.
[0057] Comparative Example 1.
[0058] An annealed B4Cp reinforced aluminum matrix composite material is prepared by the following method:
[0059] First, the composite material powder is prepared, and the process is as follows: stirring the reinforcement body in ethanol, ultrasonically dispersing the reinforcement body, wet grinding the reinforcement body, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; that is, the composite material powder is obtained;
[0060] Secondly, composite ingots were prepared by the method of "cold isostatic pressing (CIP) - vacuum packing - hot isostatic pressing (HIP)"; the final temperature of vacuum packing was 550°C, the temperature of HIP was 525°C, the time was 4h, and the pressure was 140MPa;
[0061] Third, plastic deformation processing is performed using secondary extrusion. The first extrusion is hot extrusion with a sheath, an extrusion ratio of 10:1, an extrusion temperature of 480°C, and the sheath material is 6061Al; the second extrusion is hot extrusion without a sheath, an extrusion ratio of 10:1, and an extrusion temperature of 440°C;
[0062] Fourth, strengthening and toughening heat treatment, annealing treatment; the annealing treatment process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace.
[0063] The aluminum-based composite material of this embodiment has the following components: 7.5 vol.% B4Cp, 52.5 vol.% self-made Ti-free 7000 series aluminum alloy, and 40 vol.% self-made Ti-alloyed 7000 series aluminum alloy.
[0064] The aluminum-based composite material of this comparative example has a tensile strength of 536.99 MPa in the annealed state and an elongation of 3.1%. According to the national standard GB / T 7998-2005 (determination method for intergranular corrosion of aluminum alloys), the intergranular corrosion depth is 92.3 μm ( Figure 2 ).
[0065] Comparative Example 2.
[0066] An annealed B4Cp reinforced aluminum matrix composite material is prepared by the following method:
[0067] First, the composite material powder is prepared, and the process is as follows: stirring the reinforcement body in ethanol, ultrasonically dispersing the reinforcement body, wet grinding the reinforcement body, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; that is, the composite material powder is obtained;
[0068] Secondly, the composite material ingot is prepared, which is characterized by: the composite material ingot is prepared by the method of "cold isostatic pressing (CIP) - vacuuming the jacket - hot isostatic pressing (HIP)"; the final temperature of vacuuming the jacket is 550°C, the temperature of HIP is 525°C, the time is 4h, and the pressure is 140MPa;
[0069] Third, plastic deformation processing is performed, which is characterized by: hot extrusion of the sheath, an extrusion ratio of 10:1, an extrusion temperature of 480°C, and the sheath material is 6061Al;
[0070] Fourth, strengthening and toughening heat treatment is performed by annealing; the annealing process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace.
[0071] The aluminum-based composite material of this comparative example has the following components: 7.5 vol.% B4Cp, 52.5 vol.% self-made Ti-free 7000 series aluminum alloy, and 40 vol.% self-made Ti-alloyed 7000 series aluminum alloy.
[0072] The aluminum-based composite material of this comparative example has a tensile strength of 487.67 MPa in the annealed state and an elongation of 2.1%. According to the national standard GB / T 7998-2005 (determination method for intergranular corrosion of aluminum alloys), the intergranular corrosion depth is 223.7 μm ( Figure 3 ).
[0073] Comparative Example 3.
[0074] A B4Cp reinforced aluminum matrix composite material with only one extrusion (extrusion ratio 10:1) is prepared by the following method:
[0075] First, the composite material powder is prepared, and the process is as follows: stirring the reinforcement body in ethanol, ultrasonically dispersing the reinforcement body, wet grinding the reinforcement body, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; that is, the composite material powder is obtained;
[0076] Secondly, the composite material ingot is prepared, which is characterized by: the composite material ingot is prepared by the method of "cold isostatic pressing (CIP) - vacuuming the jacket - hot isostatic pressing (HIP)"; the final temperature of vacuuming the jacket is 550°C, the temperature of HIP is 525°C, the time is 4h, and the pressure is 140MPa;
[0077] Third, plastic deformation processing is performed, which is characterized by: hot extrusion of the sheath, an extrusion ratio of 10:1, an extrusion temperature of 480°C, and the sheath material is 6061Al;
[0078] Fourth, strengthening and toughening heat treatment, using annealing treatment + solution treatment + aging treatment; the annealing treatment process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace, the solution treatment process is 460℃×2h+470℃×2h+480℃×2h+490℃×2h+500℃×2h+510℃×2h insulation and then room temperature water quenching, the aging treatment process is natural aging (T4).
[0079] The aluminum-based composite material of this comparative example has the following components: 7.5 vol.% B4Cp, 52.5 vol.% self-made Ti-free 7000 series aluminum alloy, and 40 vol.% self-made Ti-alloyed 7000 series aluminum alloy.
[0080] The aluminum-based composite material of this comparative example has a tensile strength of 540.97 MPa in the T4 (natural aging) state and an elongation of 3.3%. According to the national standard GB / T 7998-2005 (determination method for intergranular corrosion of aluminum alloys), the intergranular corrosion depth is 203.6 μm ( Figure 4 ).
[0081] Comparative Example 4.
[0082] A B4Cp reinforced aluminum matrix composite material with only one extrusion (extrusion ratio 10:1) is prepared by the following method:
[0083] First, the composite material powder is prepared, and the process is as follows: stirring the reinforcement body in ethanol, ultrasonically dispersing the reinforcement body, wet grinding the reinforcement body, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; that is, the composite material powder is obtained;
[0084] Secondly, the composite material ingot is prepared, which is characterized by: the composite material ingot is prepared by the method of "cold isostatic pressing (CIP) - vacuuming the jacket - hot isostatic pressing (HIP)"; the final temperature of vacuuming the jacket is 550°C, the temperature of HIP is 525°C, the time is 4h, and the pressure is 140MPa;
[0085] Third, plastic deformation processing is performed, which is characterized by: hot extrusion of the sheath, an extrusion ratio of 10:1, an extrusion temperature of 480°C, and the sheath material is 6061Al;
[0086] Fourth, strengthening and toughening heat treatment, using annealing treatment + solution treatment + aging treatment; the annealing treatment process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace, the solution treatment process is 460℃×2h+470℃×2h+480℃×2h+490℃×2h insulation and then room temperature water quenching, the aging treatment process is natural aging (T4).
[0087] The aluminum-based composite material of this comparative example has the following components: 7.5 vol.% B4Cp, 52.5 vol.% self-made Ti-free 7000 series aluminum alloy, and 40 vol.% self-made Ti-alloyed 7000 series aluminum alloy.
[0088] The aluminum-based composite material of this comparative example has a tensile strength of 528.24 MPa in the T4 (natural aging) state and an elongation after fracture of 3.2%.
[0089] Comparative Example 5.
[0090] A B4Cp reinforced aluminum matrix composite material with only one extrusion (extrusion ratio 10:1) is prepared by the following method:
[0091] First, the composite material powder is prepared, and the process is as follows: stirring the reinforcement body in ethanol, ultrasonically dispersing the reinforcement body, wet grinding the reinforcement body, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; that is, the composite material powder is obtained;
[0092] Secondly, the composite material ingot is prepared, which is characterized by: the composite material ingot is prepared by the method of "cold isostatic pressing (CIP) - vacuuming the jacket - hot isostatic pressing (HIP)"; the final temperature of vacuuming the jacket is 550°C, the temperature of HIP is 525°C, the time is 4h, and the pressure is 140MPa;
[0093] Third, plastic deformation processing is performed, which is characterized by: hot extrusion of the sheath, an extrusion ratio of 10:1, an extrusion temperature of 480°C, and the sheath material is 6061Al;
[0094] Fourth, strengthening and toughening heat treatment, using annealing treatment + solution treatment + aging treatment; the annealing treatment process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace, the solution treatment process is 460℃×2h+470℃×2h insulation and then room temperature water quenching, and the aging treatment process is natural aging (T4).
[0095] The aluminum-based composite material of this comparative example has the following components: 7.5 vol.% B4Cp, 52.5 vol.% self-made Ti-free 7000 series aluminum alloy, and 40 vol.% self-made Ti-alloyed 7000 series aluminum alloy.
[0096] The aluminum-based composite material of this comparative example has a tensile strength of 526.65 MPa in the T4 (natural aging) state and an elongation after fracture of 3.2%.
[0097] The parts not involved in the present invention are the same as the prior art or can be implemented by using the prior art.
Claims
1. A 600MPa strength grade high strength and high intergranular corrosion resistance B4Cp reinforced aluminum matrix composite material, characterized by: It is mainly composed of boron carbide particles (B4Cp) as reinforcement, self-made Ti-free alloyed 7000 series aluminum alloy and self-made Ti-alloyed 7000 series aluminum alloy, wherein the volume percentage of boron carbide particles (B4Cp) is 7.5 vol.%, the volume percentage of self-made Ti-free alloyed 7000 series aluminum alloy is 52.5 vol.%, and the volume percentage of self-made Ti-alloyed 7000 series aluminum alloy is 40 vol.%; the self-made Ti-free alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg) and copper (Cu), wherein the mass percentage of zinc (Zn) is 8.85%, the mass percentage of magnesium (Mg) is 2.05%, the mass percentage of copper (Cu) is 0.439%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%; The self-made Ti alloyed 7000 series aluminum alloy is mainly composed of aluminum (Al), zinc (Zn), magnesium (Mg), copper (Cu), strontium (Sr), zirconium (Zr), and titanium (Ti), wherein the mass percentage of zinc (Zn) is 11.94%, the mass percentage of magnesium (Mg) is 3.1%, the mass percentage of copper (Cu) is 1.25%, the mass percentage of strontium (Sr) is 0.0267%, the mass percentage of zirconium (Zr) is 0.249%, the mass percentage of titanium (Ti) is 1.605%, and the remainder is aluminum and a small amount of impurity elements; the sum of each component is 100%.
2. A method for preparing the 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material according to claim 1, characterized in that it The process includes: (1) preparing composite material powder; (2) preparing composite material ingot; (3) plastic deformation processing; (4) strengthening and toughening heat treatment; The composite material powder is prepared by stirring the boron carbide particle reinforcement in ethanol, ultrasonically dispersing the boron carbide particle reinforcement, wet grinding the boron carbide particle reinforcement, adding self-made Ti-free alloyed 7000 series aluminum alloy powder for wet grinding, drying, dry grinding, sieving powder, adding self-made Ti-alloyed 7000 series aluminum alloy powder for dry grinding, sieving powder again, and vacuum drying; the composite material powder is obtained; The composite material ingot is prepared by a method of "cold isostatic pressing (CIP) - vacuuming the package - hot isostatic pressing (HIP)"; the final temperature of vacuuming the package is 550°C, the temperature of HIP is 525°C, the time is 4 hours, and the pressure is 140MPa; The plastic deformation process is as follows: secondary extrusion, the first extrusion is hot extrusion with a sheath, the extrusion ratio is 10:1, the extrusion temperature is 480°C, and the sheath material is 6061Al; the second extrusion is extrusion without a sheath, the extrusion ratio is 10:1, and the extrusion temperature is 440°C; The strengthening and toughening heat treatment refers to: annealing treatment + solution treatment + aging treatment; the annealing process is 250℃×6h+350℃×6h+450℃×12h insulation and then cooling with the furnace, and the solution treatment process is: 460℃×2h+470℃×2h+480℃×2h+490℃×2h or 460℃×2h+470℃×2h+480℃×2h+490℃×2h+500℃×2h+510℃×2h or 460℃×2h+470℃×2h+480℃×2h, water quenching at room temperature after insulation, and natural aging treatment process; 600MPa strength grade high-strength and high intergranular corrosion resistance B4Cp reinforced aluminum-based composite material can be obtained.
Citation Information
Patent Citations
600-650 MPa high-strength intergranular corrosion resistant aluminum alloy and preparation method thereof
CN104004947A
Boron carbide aluminum matrix composite material and preparation method thereof
CN106702192A